2009
DOI: 10.1055/s-0029-1211742
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the time-action profiles of U40- and U100-regular human insulin and the rapid-acting insulin analogue B28 Asp

Abstract: It is well known that rapid-acting insulin analogues like insulin aspart (B28Asp) show a faster onset and a shorter duration of action than currently available U100 soluble insulin preparations. Since this effect is mainly due to a lower concentration of slow-absorbable hexamers, the metabolic profile of human insulin in lower concentration (e.g. U40 insulin) might be more similar to that of insulin aspart. Therefore, we compared the pharmacodynamic and pharmacokinetic properties of U40 soluble insulin with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…Our results confirm the faster onset of action and the shorter duration of action of IAsp for a wide dose range observed with lower insulin doses (0.1-0.2 U/kg) in previous studies [5,7,[19][20][21]. Our results confirm the faster onset of action and the shorter duration of action of IAsp for a wide dose range observed with lower insulin doses (0.1-0.2 U/kg) in previous studies [5,7,[19][20][21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results confirm the faster onset of action and the shorter duration of action of IAsp for a wide dose range observed with lower insulin doses (0.1-0.2 U/kg) in previous studies [5,7,[19][20][21]. Our results confirm the faster onset of action and the shorter duration of action of IAsp for a wide dose range observed with lower insulin doses (0.1-0.2 U/kg) in previous studies [5,7,[19][20][21].…”
Section: Discussionsupporting
confidence: 91%
“…Rapid-acting insulin analogues such as IAsp have been designed to mimic physiological insulin secretion more closely, thereby leading to lower postprandial blood glucose excursions in DIABETES, OBESITY AND METABOLISM original article comparison with RHI. Our results confirm the faster onset of action and the shorter duration of action of IAsp for a wide dose range observed with lower insulin doses (0.1-0.2 U/kg) in previous studies [5,7,[19][20][21]. This body of evidence suggests that IAsp has significant advantages over RHI in covering prandial insulin requirements even when high doses are used.…”
Section: Discussionsupporting
confidence: 90%
“…A range of studies have described concentration‐dependent absorption kinetics of subcutaneous bolus injection of human insulin . The different studies concerning human insulin, in different concentrations, showed varying outcomes . Several studies displayed a difference between U40 and U100 human insulin while others failed to do so .…”
Section: Discussionmentioning
confidence: 99%
“…insulin lispro and insulin aspart) had a faster onset of action and a shorter duration of action compared to both human insulin formulations. Furthermore, the pharmacokinetic and pharmacodynamic profile of human insulin U40 almost overlaps that of human insulin U100, while a more rapid increase for the lower concentration was not confirmed . In contrast, a second study concluded that human insulin U40 was closer to the rapid‐acting analogue than human insulin U100 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation